2001
DOI: 10.1021/es001203q
|View full text |Cite
|
Sign up to set email alerts
|

A Kinetic Study of Nickel Complexation in Model Systems by Adsorptive Cathodic Stripping Voltammetry

Abstract: Adsorptive cathodic stripping voltammetry (AdCSV) in conjunction with the competing ligand-exchange method (CLEM) was investigated as a tool for measuring dissociation rate coefficients of nickel complexes in model systems. Dimethylglyoxime (DMG) was used as the competing ligand. Citric acid (CA) and a well-characterized fulvic acid (FA) were used as model ligands. The rate coefficients were calculated, and the consistency of equilibrium and kinetic data was discussed. The contributions of the disjunctive path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 25 publications
(36 reference statements)
0
8
0
Order By: Relevance
“…Because the ligand exchange rate is a function of the initial ligand concentration (citrate), the ligand exchange rate can be substantially influenced by other factors, including metal and initial metal-binding ligands ratios (Hering and Morel, 1990;Celo et al, 2001). Dissolved Fe is buffered by the excess unknown organic ligands in oceanic waters .…”
Section: Geochemical Implication Of Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…Because the ligand exchange rate is a function of the initial ligand concentration (citrate), the ligand exchange rate can be substantially influenced by other factors, including metal and initial metal-binding ligands ratios (Hering and Morel, 1990;Celo et al, 2001). Dissolved Fe is buffered by the excess unknown organic ligands in oceanic waters .…”
Section: Geochemical Implication Of Findingsmentioning
confidence: 99%
“…In the ligand exchange reaction between a siderophore and organically complexed Fe(III) (hereafter, referred to as incoming ligand and initial FeL complex, respectively), the Fe-siderophore formation proceeds as a second-order reaction with respect to the concentrations of these two molecules (Ito et al, 2011). In this process, two major pathways have been proposed to occur concurrently: (i) the adjunctive pathway, in which an incoming ligand directly associates with the FeL complex, followed by dissociation of the initial ligand (L) from the metal center via intermediate ternary complex formation and (ii) the disjunctive pathway in which unchelated Fe(III) forms via thermal dissociation of the FeL complex then reacts with an incoming ligand (Hering and Morel, 1990;Schuman, 1992;Celo et al, 2001). In the latter pathway, the reaction rate is a function of initial ligand concentration since the unchelated Fe(III) is buffered by the excess initial ligand, whereas the rate of the former pathway is independent of the initial ligand concentration as the incoming ligand directly associates with the intact FeL complex (prior to any dissociation of FeL).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In earlier studies slow dissociation kinetics 80 of natural Ni-DOM complexes have been demonstrated [6,10,[13][14][15][16], however no data were 81 found on association kinetics. We used the Donnan speciation technique [17], a method which 82 minimizes the disturbance of the equilibrium composition in the test solution and which does 83 not rely on a priori knowledge of the conditional stability constant of a competing ligand.…”
Section: Page 11 Of 31mentioning
confidence: 99%
“…In cases where siderophore-mediated uptake is important, exchange of the ligand binding Fe(III) in bulk solution for the siderophore must occur with the precise mechanism, and the rate of this exchange process is strongly dependent upon both the nature of the ligands and on solution conditions such as pH and ligand/metal concentration ratio. Over the last few decades, the kinetics of the ligand exchange process has been investigated for a range of metals (e.g., Fe, Cu, Al, Cd, Pb, and Ni) and ligands (e.g., dimethylglyoxime, lumogallion, citrate, nitrilotriacetic acid, ethylenediaminetetraacetic acid, 3-hydroxy-1,2-dimethyl-4-pyridone, desferrioxamine B, and humic and fulvic acids) and found to be second-order for selected metals (e.g., Cu, Al, and Ni) in terms of metal–ligand complex and incoming ligand concentrations at various pH and ionic strength. For metal–ligand complexes with 1:1 binding stoichiometry, the rate of substitution by the incoming ligand may be accounted for via two simultaneous reaction pathways, i.e., disjunctive and adjunctive. In the disjunctive pathway, the initial metal–ligand complex first dissociates to form the liberated or unchelated metal followed by the subsequent complexation by the incoming ligand.…”
Section: Introductionmentioning
confidence: 99%